To generate greater economic benefits from visiting ships - Chen, Sixuan (2018)
The strategic location of Singapore has made the island country a successful maritime hub and maritime-related businesses have long been a crucial composition of Singapore’s economy. While the global seaborne trade is still recovering after the catastrophic economic downturn, port of Singapore has seen little growth in recent years (UNCTAD, 2017). With the emergence of alternative trade routes and rising competition from neighbouring countries, Singapore is facing a challenge to maintain its position. Therefore, it is crucial to strengthen its position as a global maritime hub and explore methods to generate greater economic benefits from visiting ships. To generate greater economic benefits, one approach is to increase efficiency of the current processes and to increase efficiency, we cannot avoid talking about automation and digitalisation. With recent developments in Information Technology, industries such as manufacturing, logistics and retail are going through a revolution. Information is now shared through online platforms, payments are done by online systems and some work which used to require human inputs are now performed by robots. All these changes help to save labour cost and increase productivity and hence contribute to a higher efficiency of performing different tasks. Automation and digitalisation have greatly changed the way we do business and the results have proven that we have taken the right path. One way that digitalisation has transformed industries is through the creation and application of different digital platforms. There are many types of platforms depending on the users of the platform, for example, Amazon is a platform where shoppers interact with retailers, PayPal is the platform where payers interact with payees and Google is the platform where internet users interact with advertisers. The platforms bring many benefits to the industry such as lower operating cost and broader customer base. The potential users from marine service industry are business organisations including service providers and service users. Therefore, among all the different type of platforms, a B2B e-commerce platform is most suitable for the industry. This part of the research focuses on the possibility of developing a B2B e-commerce platform for the marine service industry in Singapore. Research was done to get better understanding of the idea and interviews were conducted to gain insights from the industry. Following that, a SWOT analysis was done to identify the strengths and weaknesses of this solution and opportunities and threats that may be faced by the solution. The potential difficulties in developing the solution and expected benefits of successful development were also listed out. In a nutshell, this report presents an optimistic outlook for the B2B e-commerce solution. With efforts made by relevant industry players, the B2B e-commerce solution has great potential to generate more economic benefits to Singapore.